Overview of Thesis Writing Guidelines for The Faculty of Law, Syiah Kuala University and Its Relation to Johny Ibrahim's Normative Legal Research Methods - Bakti Bakti; Muhammad Saleh (Syiah Kuala Law Journal, 2021)
This paper is intended to understand the description and characteristics of legal research produced by law faculty students and developed by law scientists and researchers at Syiah Kuala University as a sample case. Does the description of the research results of legal researchers, including students and legal scientists, follow the characteristics and legal paradigms that tend to be classical or have they led to the development of contemporary legal theories.